2022
DOI: 10.3390/metabo12040347
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Supplementation in Beef Cattle and Its Effects on Plasma Metabolome of Dams and Calves

Abstract: This study investigated the effect of different prenatal nutrition on the plasma metabolome of Nellore dams and their offspring. For that purpose, three nutritional treatments were used in 126 cows during pregnancy: NP—(control) only mineral supplementation; PP—protein-energy supplementation in the final third; and FP—protein-energy supplementation during the entire pregnancy. Targeted metabolomics were analyzed in plasma at the beginning of pregnancy and in pre-delivery of cows (n = 27) as well as in calves (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Meanwhile, beta-alanine can maintain the antioxidant capacity of the body [83], and the increase in beta-alanine could be an indicator of improved milk quality. Similarly, previous studies suggested that beta-alanine supplementation improved growth performance, meat quality, and antioxidant capacity, and also affected amino acid metabolism on broiler chickens [84], dairy cows [85]. One key role of beta-alanine in sheep ovarian physiology is in the regulation of follicular development, which is regulated by various hormones and growth factors.…”
Section: Discussionmentioning
confidence: 91%
“…Meanwhile, beta-alanine can maintain the antioxidant capacity of the body [83], and the increase in beta-alanine could be an indicator of improved milk quality. Similarly, previous studies suggested that beta-alanine supplementation improved growth performance, meat quality, and antioxidant capacity, and also affected amino acid metabolism on broiler chickens [84], dairy cows [85]. One key role of beta-alanine in sheep ovarian physiology is in the regulation of follicular development, which is regulated by various hormones and growth factors.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, L-carnosine has been found to inhibit cell death and modulate mitochondrial energy metabolism in neuron cultures subjected to oxygen-glucose deprivation ( Ouyang et al., 2016 ). In a study conducted by Schalch Junior et al. (2022) , it was reported that prenatal protein-energy supplementation throughout the entire duration of pregnancy in beef cattle leads to alterations in serum L-carnosine levels in the resulting calves.…”
Section: Discussionmentioning
confidence: 99%
“…These plans were the following treatments programs: (NP) non-programming, where cows received only a mineral supplementation equivalent to 0.3 g/kg of body weight (BW); partially programming (PP), which included supplementation with protein energy supplementation at 3 g/kg of BW during the last third of pregnancy; and complete programming (CP), where the cows received 3 g/kg of BW of protein energy supplementation from the moment of pregnancy confirmation (30 days after FTAI) until birth. For further details on the treatments, see Schalch Junior et al [ 10 ].…”
Section: Methodsmentioning
confidence: 99%